A Bibliometric Analysis: Public Health in Germany during COVID-19 - Karissa Ardelia Abieza Nugraha; Achmad Nurmandi; Aulia Nur Kasiwi (Universitas Pancasakti Tegal, 2023)
This study aims to find out how the German state policy strategy in dealing with COVID-19. COVID-19 is a global problem that is being faced by various countries in the world as well as the biggest health crisis of the 21st century. Throughout 2020 until now the world has been shocked by the emergence of a new virus that is infecting the world today, namely COVID-19. The COVID-19 pandemic has also had a major impact on the country in controlling the spread of COVID-19 effectively. This study is based on a bibliometric review of sustainability studies, related to case studies of handling Covid-19 in Germany. The data obtained and processed are then analyzed using qualitative analysis techniques, namely analyzing to obtain an overview and categories to be patterned. Germany was one of the countries affected by the initial period of the virus emerged in Europe. After realizing the fatal consequences, the German Government carried out an integrative national policy to overcome it, until Germany slowly emerged from the crisis.